PENGEMBANGAN KURIKULUM PENDIDIKAN AGAMA ISLAM MODEL KURIKULUM 2013 DI SD MUHAMMADIYAH YOGYAKARTA - RR. Ninik Barokatul Khasanah; Hendro Widodo (Universitas Muhammadiyah Ponorogo, 2019)
The curriculum is a reference component for each education unit and directs all forms of educational activities to achieve educational goals. The curriculum becomes an absolute requirement of education and becomes an integral part of education and teaching.Muhammadiyah Jogokariyan Elementary School Yogyakarta is one of Muhammadiyah's Business Charities under the Regional Education Council of Muhammadiyah Yogyakarta Regional Leaders also uses 2 curricula (government curriculum and Muhammadiyah Yogyakarta Regional Leadership curriculum).One of the curriculums developed at Muhammadiyah Jogokariyan Elementary School in Yogyakarta is about memorizing the Qur'an, thank God that with Tahfidz every year his students always increase and gain the trust of the community.